The True Grand Challenge for Engineering: Self-Knowledge - Mitcham, Carl (Online Ethics Center, 2019)
In 2003, the National Academy of Engineering (NAE) published A Century of Innovation celebrating "20 engineering achievements that transformed our lives" across the 20th century, from automobiles to the Internet. Five years later, it followed up with 14 Grand Challenges for engineering in the 21st century, including making solar energy affordable, providing energy from fusion, securing cyberspace, and enhancing virtual reality. But only the most cursory mention was made of the greatest challenge of all: cultivating deeper and more critical thinking, among engineers and nonengineers alike, about the ways engineering is transforming how and why we live.
Published Work
Keywords: Social Responsibility; Goals of Ethics Education